Youth Subcultures in Postwar and Contemporary Fiction - Bentley, Nick. author. (orcid)0000-0002-3096-9002 Link aut Link
X, 315 p.
Keywords: This book offers a unique interdisciplinary examination of how youth subcultures have been articulated and constructed in selected fiction from the post-war period to the twenty-first century. It provides a theoretical underpinning for the analysis of subcultures and scenes in literary fiction, identifying approaches set against key theories from subcultural studies, sociology, and criminology as well as paying close attention to issues of literary form, genre and narrative technique. As well as identifying an overlooked body of work in postwar and contemporary fiction, it shows how literary fiction can offer a distinctive contribution to our understanding of youth and marginalized cultures. It offers close analysis of a range of novels organized around key themes and contexts including teenagers, Teds and jazz scenes in the 1950s; Beat writing and the counterculture; punk fiction; dystopian and cyberpunk fiction as well as the examination of works that foreground class, race, gender and sexuality. Nick Bentley is Reader in English Literature at Keele University, UK. He is a leading expert in postwar and contemporary fiction, particularly in the literatures of class and marginalization. He is author of Contemporary British Fiction: A Reader’s Guide to the Essential Criticism (2018); Martin Amis (2015); Contemporary British Fiction (2008); Radical Fictions: The English Novel in the 1950s (2007); and co-editor of The 2000s: A Decade of Contemporary British Fiction (2015), The 1950s: A Decade of British Fiction (2018) and Teenage Dreams: Youth Subcultures in Fiction, Film and Other Media (2018).